PERAN EVALUASI KARYAWAN DALAM PERENCANAAN SUMBER DAYA MANUSIA STRATEGIS PADA KLINIK TUMBUH KEMBANG ANAK DI ERA DIGITAL KOTA BANJARMASIN - Putri, Marella Indira; Zakky Zamrudi; Syahrial Shaddiq (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to analyze the role of employee evaluation in supporting strategic Human Resource (HR) planning at the Child Development Clinic in the digital era and to examine the implementation of digital-based evaluation systems in improving HR management effectiveness. As a therapy service provider for children with special needs, the clinic requires professional and consistent human resources capable of delivering services aligned with each child’s developmental needs. This research employs a descriptive qualitative approach involving key informants such as the clinic director, therapy coordinator, therapists, HR administrative staff, and parents of patients. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings reveal that employee evaluation plays a crucial role in competency mapping, identifying training needs, and developing relevant HR strategies. Performance evaluation also enhances service quality, strengthens objectivity, and promotes therapist professionalism. Moreover, the implementation of a digital evaluation system is perceived to improve data management effectiveness, accelerate assessment processes, and enhance accuracy and transparency. Digital transformation in employee evaluation contributes significantly to long-term HR planning and the improvement of therapy service quality. Therefore, the digitalization of performance evaluation serves as a strategic measure for the clinic to establish a more adaptive, modern, and quality-oriented HR management system.